Sex- and Gender-specific Analysis in Orthopaedic Studies. Issue 7 (July 2020) - Gianakos, Arianna L.; George, Nicole; Pinninti, Angelica; Kwan, Stephanie; LaPorte, Dawn; Mulcahey, Mary K.
Abstract: Background: Orthopaedic studies have reported the prevalence of injuries and outcomes after treatment in men and women patients, and although these differences have been recognized, few studies have evaluated for gender-specific injury patterns, disease progression, and treatment outcomes. A thorough understanding of gender-related differences is important to better individualize treatment and improve outcomes. Questions/purposes: In this study, we sought (1) to determine the proportion of studies published in six orthopaedic journals that provided sex- or gender-specific analyses in 2016 and whether a difference was found in outcomes between men and women and (2) to evaluate whether this proportion varied across several orthopaedic subspecialty journals or between general orthopaedic journals and subspecialty journals. Methods: Six leading orthopaedic surgery journals were selected for review, including two general orthopaedic journals ( Journal of Bone and Joint Surgery and Clinical Orthopaedics and Related Research ®) and four subspecialty journals ( American Journal of Sports Medicine, Journal of Arthroplasty, Journal of Shoulder and Elbow Surgery, and Spine ). Journal issues published in the even-numbered months of 2016 were reviewed for clinical randomized controlled, cohort, and case-control studies in which women were a part of the study population. A total of 712 studies evaluating 24, 607, 597 patients met the criteria and were included in our review of publications from 2016. The selected studies were stratified based on whether gender was a variable in a multifactorial statistical model. Outcomes of interest included the proportion of patients who were women and the presence or absence of a gender-specific analysis. These endpoints were compared between journals. Results: Overall, 55% (13, 565, 773 of 24, 607, 597) of patients analyzed in these studies were women. Only 34% (241 of 712) of the studies published in 2016 included gender as variable in a multifactorial statistical model. Of these, 39% (93 of 241) demonstrated a difference in the outcomes between patients who were men and women. The Journal of Arthroplasty had the greatest percentage of patients who were women (60%, 9, 251, 068 of 15, 557, 187) and the American Journal of Sports Medicine had the lowest (44%, 1, 027, 857 of 2, 357, 139; p < 0.001). Orthopaedic subspecialty journals tended to include a greater percentage of women (54%) than did general orthopaedic journals (50%; p = 0.04). Conclusion: Currently, it is unclear what percentage of published orthopaedic studies should include a gender-specific analysis. In the current study, more than one-third of publications that performed a gender-specific analysis demonstrated a difference in outcomes between men and women, thereby emphasizing the need to determine when such an analysis is warranted. Clinical Relevance: Future studies should aim to determine when a gender-specific analysis is necessary to improve the management of orthopaedic injuries in men and women. It is important for investigators at the individual-study level to look for every opportunity to ensure that both men's and women's health needs are met by performing appropriate by-sex and by-gender analyses, but not to perform them when they are unnecessary or inappropriate.